Effect of Ni doping in NixMn1−xTi10 (x = 0.1–0.5) on activity and SO2 resistance for NH3-SCR of NO studied with in situ DRIFTS. Issue 15 (30th June 2017) - Chen, Liqiang; Li, Rui; Li, Zhibin; Yuan, Fulong; Niu, Xiaoyu; Zhu, Yujun
Abstract : The Ni0.4 Mn0.6 Ti10 catalyst exhibits excellent SO2 resistance, high NO conversion and N2 selectivity in the range of 190–360 °C even in the presence of 100 ppm SO2 and 15% H2 O under a GHSV of 40 000 h −1 due to the interaction among Mn, Ni and Ti oxides. Abstract : In this work, a series of Ni x Mn1− x Ti10 ( x = 0.0–0.5) catalysts were synthesized using a one-pot sol–gel method for selective catalytic reduction (SCR) of NO with NH3 . The effects of Ni doping on the catalytic activity and SO2 resistance were investigated by XRD, TEM-EDS, XPS, NH3 -TPD, H2 -TPR, SO2 -TPD and in situ DRIFTS. It is found that the higher the amounts of surface Mn 4+ and Oα species existing on the catalyst surface, the greater the oxidation ability that they present for NO and NH3, which results in better activity at low temperature and worse selectivity to N2 at high temperature due to the overoxidation of NH3 . Among Ni x Mn1− x Ti10 ( x = 0.0–0.5), the Ni0.4 Mn0.6 Ti10 catalyst exhibited excellent NH3 -SCR activity, a wide temperature window (190–360 °C) and good H2 O and SO2 durability even in the presence of 100 ppm SO2 and 15% H2 O under a GHSV of 40 000 h −1, which is very competitive for the practical application in controlling the NO x emission from stationary sources. It is concluded that more surface Lewis acid sites and the appropriate contents of surface active Mn 4+ and surface oxygen species on the surface of Ni0.4 Mn0.6 Ti10 play key roles in the special SCR performance due to the interactions among Mn, Ni and Ti oxides. The SO2 -TPD and in situ DRIFTS results confirm the reason for the good SO2 resistance of the Ni0.4 Mn0.6 Ti10 catalyst. Moreover, in situ DRIFTS results reveal that the NH3 -SCR reaction over Ni0.4 Mn0.6 Ti10 mainly follows the Eley–Rideal (E–R)-type mechanism.